2023
DOI: 10.1037/pha0000540
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol craving in the natural environment: Moderating roles of cue exposure, drinking, and alcohol sensitivity.

Abstract: Effects of cue exposure and alcohol consumption (e.g., priming doses) on craving for alcohol have been examined in largely separate literature, limiting what is known about their potential interaction. Individuals with low alcohol sensitivity, a known risk factor for alcohol use disorder (AUD), exhibit stronger cueelicited craving than their higher-sensitivity (HS) peers in both laboratory and real-world contexts. Here, underage drinkers (N = 155) completed a 21-day ecological momentary assessment (EMA) protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 116 publications
2
17
0
Order By: Relevance
“…Eligibility criteria were (a) being age 18–20, (b) endorsing at least monthly alcohol use, (c) endorsing a binge drinking episode in the past 6 months, (d) being able to read and write in English, and (e) normal or corrected-to-normal vision. Study exclusion criteria were a history of (a) attempting to quit/reduce drinking, (b) neurological disease, or (c) head injuries with a loss consciousness of >2 min (for more details, see Cofresí et al, 2022; Kohen et al, 2022). For the present study, participants were included if they reported at least one drinking episode during ecological momentary assessment (EMA) and had at least one report of day-level drinking motives.…”
Section: Methodsmentioning
confidence: 99%
“…Eligibility criteria were (a) being age 18–20, (b) endorsing at least monthly alcohol use, (c) endorsing a binge drinking episode in the past 6 months, (d) being able to read and write in English, and (e) normal or corrected-to-normal vision. Study exclusion criteria were a history of (a) attempting to quit/reduce drinking, (b) neurological disease, or (c) head injuries with a loss consciousness of >2 min (for more details, see Cofresí et al, 2022; Kohen et al, 2022). For the present study, participants were included if they reported at least one drinking episode during ecological momentary assessment (EMA) and had at least one report of day-level drinking motives.…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol cue reactivity is also shown in prior ecological research (Kohen et al, 2022;Miranda Jr. et al, 2013;Padovano & Miranda Jr, 2021;Trela et al, 2018), though real-world data are less abundant for underage drinkers and for alcohol (but see also Kohen et al, 2022), relative to older drinkers and other addictive substances (e.g., nicotine). In youths' daily lives, all alcohol-related cues, whether social context (i.e., presence of peers) or visible alcohol cues (e.g., bottle in real life, online image), elicited greater craving than when these cues were not present.…”
Section: Discussionmentioning
confidence: 70%
“…Future work should consider whether personality traits moderate the associations between the presence of peers and youth alcohol craving. Considering recent work demonstrating that in youth 18 to 20 years old, cue‐elicited craving was a stronger predictor of craving during postdrinking moments (compared to nondrinking moments; Kohen et al, 2022), future work may wish to examine potential age‐related differences in associations between social‐context cues and craving in postdrinking moments. Biological sex covariates in relation to craving were marginal within the current sample, which contrasts with some research suggesting that sex differences and psychosocial gender differences may be relevant for understanding alcohol craving (Holzhauer et al, 2020; Moeller, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one study found that young adults ( N = 42; ages 15 to 20 years) completing two assessments per day for 2 weeks consumed greater quantities of alcohol the same day that they experienced higher average levels of craving (Ramirez & Miranda, 2014). Another study reported that, among underage drinkers ( N = 155; ages 18 to 20 years) who completed a 21‐day EMA protocol, cue‐induced craving was increased in postdrinking moments compared with nondrinking moments (Kohen et al, 2022). Our group found that, among young adults with hazardous drinking ( N = 93; ages 18 to 25 years), increases in desire to get drunk above a person's mean value on a typical drinking day were associated with greater likelihood of binge drinking (Suffoletto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%